Explicitation and Implicitation in Legal Translation – A Process Study of Trainee Translators - Hjort-Pedersen, Mette; Faber, Dorrit (Meta, 2010)
This article explores the use of explicitation and implicitation in the context of legal translation. Legal texts are linguistically complex and difficult to understand for lay persons. From a cognitive point of view it may therefore be assumed that ex- and implicitations will be frequent phenomena in legal TTs, because translators will tend to leave traces of their hard-won understanding in the TT. On the other hand, legal translations have legal consequences in the real world. From a legal point of view it may therefore conversely be assumed that ex- and implicitations will be relatively rare phenomena in legal TTs because of the potential legal effect of adding or removing information. But how is this schism reflected in legal TTs performed by translators at different levels of expertise? This article examines phenomena of ex- and implicitations in trainee translator TTs. It is hypothesized that lack of sufficient knowledge of legal scenarios will override heavy mental processing efforts and that trainee translators will restrict themselves to choosing only obligatory ex- and implicitations as their safe bet.